Tingkat Kepuasan Pasien terhadap Pelayanan di Poliklinik Gigi Rumah Sakit Hermina Manado - Jequline M. Sagay; Risqa R. Darwita; Herry Novrinda (e-GiGi, 2023)
Abstract: Good service quality is closely related to patient satisfaction in health care, one of its indicators is patient satisfaction with health services provided by dentists. The Servqual dimension and the Donabedian domain are benchmarks for measuring service quality as well as a comparison of perceptions and expectations of patient satisfaction. Patient satisfaction with health services will have an impact on the health and welfare of society. This study aimed to determine the level of patient satisfaction with the service and treatment of dental and oral diseases at the Dental Clinic of Hermina Manado Hospital. This was a quantitative study with a cross sectional design using convenience sampling with a total sample of 105 respondents. Google form questionnaire or document as an instrument. The results of univariate and bivariate analysis used a correlation test showed the average patient satisfaction of 33.27 (±5.95) with a satisfied percentage of 78.1% and dissatisfied of 21.9%. The bivariate analysis of respondent characteristics showed significant relationships between age, marital status, occupation, payment method and waiting time with patient satisfaction (p<0.05), and there was a significant relationship with a very strong linear correlation between service quality seen from the five dimensions of Servqual and the Donabedian domain with the level of patient satisfaction in the dental clinic at Hermina Manado Hospital. In conclusion, good service quality is positively related to patient satisfaction in performing dental treatment. Good structure improves process and good results. Keywords: satisfaction patient; dental care; hospital; service quality   Abstrak: Kualitas pelayanan yang baik berhubungan erat dengan kepuasan pasien dalam perawatan kesehatan; salah satu indikatornya ialah kepuasan pasien terhadap pelayanan kesehatan yang diberikan oleh dokter gigi. Dimensi Servqual dan domain Donabedian menjadi tolak ukur untuk mengukur kualitas pelayanan serta perbandingan persepsi dan harapan terhadap kepuasan pasien. Kepuasan pasien akan pelayanan kesehatan akan berdampak pada kesehatan dan kesejahteraan masyarakat. Penelitian ini bertujuan untuk mengetahui tingkat kepuasan pasien terhadap pelayanan dan perawatan penyakit gigi dan mulut di Poliklinik  Gigi RS Hermina. Jenis penelitian ialah potong lintang dengan convenience sampling, total sampel 105 responden. Metode penelitian yaitu kuantitatif. Kuesioner Google form atau dokumen sebagai instrumen penelitian. Hasil analisis univariat dan bivariat menggunakan uji korelasi mendapatkan rerata kepuasan pasien 33,27 (±5,95) serta persentasi puas 78,1% dan tidak puas 21,9%. Analisis bivariat karakteristik responden mendapatkan hubungan bermakna antara usia, status marital, pekerjaan, metode pembayaran dan waktu tunggu dengan kepuasan pasien (p<0,05) dan terdapat hubungan bermakna dengan korelasi linear sangat kuat antara kualitas pelayanan dilihat dari lima dimensi Servqual dan domain Donabedian dengan tingkat kepuasan pasien di Poliklinik  Gigi RS Hermina Manado. Simpulan penelitian ialah kualitas pelayanan yang baik berhubungan positif terhadap kepuasan pasien dalam melakukan perawatan gigi. Struktur yang baik meningkatkan proses dan hasil yang baik. Kata kunci: kepuasan pasien; perawatan gigi; rumah sakit; kualitas pelayanan